2014
DOI: 10.1038/bjc.2014.208
|View full text |Cite
|
Sign up to set email alerts
|

Does change in health-related quality of life score predict survival? Analysis of EORTC 08975 lung cancer trial

Abstract: Background:Little is known about whether changes in health-related quality of life (HRQoL) scores from baseline during treatment also predict survival, which we aim to investigate in this study.Methods:We analysed data from 391 advanced non-small-cell lung cancer (NSCLC) patients enrolled in the EORTC 08975 study, which compared palliative chemotherapy regimens. HRQoL was assessed at baseline and after each chemotherapy cycle using the EORTC QLQ-C30 and QLQ-LC13. The prognostic significance of HRQoL scores at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 36 publications
5
73
1
3
Order By: Relevance
“…The EORTC 08975 study including patients with advanced non-small-cell lung cancer subjected to chemotherapy showed that a high level of symptoms presented by patients at baseline was associated with a poor prognosis. Higher scores of physical functioning, pain, dysphagia as components of healthrelated quality of life and WHO performance status were associated with lower risk of death (9,11). In another study by Braun et al, the physical function was predictive of survival independent of other components of quality of life.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The EORTC 08975 study including patients with advanced non-small-cell lung cancer subjected to chemotherapy showed that a high level of symptoms presented by patients at baseline was associated with a poor prognosis. Higher scores of physical functioning, pain, dysphagia as components of healthrelated quality of life and WHO performance status were associated with lower risk of death (9,11). In another study by Braun et al, the physical function was predictive of survival independent of other components of quality of life.…”
Section: Discussionmentioning
confidence: 95%
“…Research shows that improvement in quality of life components reduces the risk of death in patients with lung cancer. Quality of life is an important factor because it affects survival; thus, it can be considered as a prognostic factor for shorter survival (9)(10)(11). Pain is one of the most important symptoms reported by cancer patients.…”
Section: Original Articlementioning
confidence: 99%
“…Mortality rates for this cancer type are high, with 1-and 5-year survival of 42% and 16%, respectively [2]. Lung cancer is associated with higher symptom burden compared to other cancers and treatment-related symptoms are associated with clinical outcomes including disease-free and overall survival (OS) and treatment success [3,4]. Symptoms such as fatigue, chest pain and persistent cough frequently exist before diagnosis and may impact health-related quality of life (HRQOL) [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Given the standard of 10 or more events per covariate included in a multivariable Cox Proportional Hazards model, our models with 18 covariates were appropriate. 14 We performed sensitivity analyses reducing the number of socioeconomic factors and comorbidities adjusted for in both models, which yielded similar results. We computed adjusted odds ratios (OR), hazard ratios (HR) and 95% confidence intervals (CI) for each estimate.…”
Section: Methodsmentioning
confidence: 83%